Real-time membrane fouling analysis for the assessment of reclamation potential of textile wastewater processed by membrane distillation. (October 2021) - Elcik, Harun; Fortunato, Luca; Vrouwenvelder, Johannes S.; Ghaffour, Noreddine
Abstract: Understanding the factors that specify the fouling development in membrane distillation (MD) plays a key role to develop effective control strategies with the aim of providing its widespread use in industrial applications, such as textile industry. The present study investigated the fouling mechanisms in textile wastewater treatment by direct contact MD (DCMD), employing an advanced in-situ optical coherence tomography (OCT) technology allowing to monitor MD fouling in real-time. The OCT analysis enabled evaluating the effect of feed temperature, flow rate, dye concentration on the membrane fouling and the long-term performance of MD operation that includes a periodical water flushing. The permeate flux decrease during the initial stages of experiments was attributed to the existence of attractive hydrophobic-hydrophobic interaction between the membrane and dye molecules as no cake fouling was observed at the early stages. Then, a flat and homogeneous cake layer was developed with time in all the fouled membranes regardless of the cake layer thickness. The long-term experiment resulted in both reversible and irreversible fouling and showed that water flushing had limited efficacy against reversible fouling. Additionally, electrostatic repulsive forces occurring between the membrane and textile dye molecules influenced the permeate flux depending on the dye concentration. Finally, among all the operating parameters, feed temperature had the highest impact on the membrane fouling and process performance, changed the heat transfer activity at the membrane-liquid frontier zone, in turn, leading to variations in the flux. Graphical abstract: Unlabelled Image Highlights: The fouling mechanisms in textile wastewater treatment by DCMD were investigated. OCT allowed monitoring MD fouling non-destructively in real-time. The structure of the MD fouling consisted of a flat and homogeneous cake layer. Feed temperature had the highest impact on MD fouling and process performance. Water flushing was not effective in removing the organics.